Kebiri Kimia sebagai Sanksi bagi Pelaku Kejahatan Pedofilia: Telaah Maqasid Syariah dan Prinsip Non-Diskriminasi HAM - Atifah, Nurul Rezeki; Marilang, Marilang; Hamsir, Hamsir (Universitas Islam Negeri Alauddin Makassar, 2025)
The purpose of this study is to evaluate the extent to which chemical castration is effective in providing a deterrent effect, analyze the argumentative basis of this punishment as a form of prevention, and assess its conformity with the principles of human rights and Islamic criminal law. This article examines the application of chemical castration punishment to perpetrators of sexual crimes, especially pedophilia, through the perspective of Human Rights (HAM) and Islamic criminal law. The background of this study is based on the increasing cases of sexual violence in Indonesia which encourages the government to adopt chemical castration as a repressive and preventive effort. This research uses a literature study method with an exploratory-qualitative approach. Data were collected through document analysis, positive legal literature, international provisions related to human rights, as well as authoritative sources in classical and contemporary Islamic law. The analysis was carried out normatively and descriptive-critically. The results of the study show that chemical castration punishment causes controversy from various aspects, both medically, psychologically, socially, and legally. From a human rights perspective, this action is seen as a form of treatment that degrades human dignity and has the potential to violate the principle of non-derogable rights related to physical and mental integrity. Meanwhile, from the perspective of Islamic criminal law, although there is a principle of prevention ('sadd al-dzari'ah') against crime, there is no explicit legitimacy that allows invasive medical measures such as chemical castration, which can be categorized as a form of mutilation and is not in line with maqāṣid al-syarī'ah in safeguarding body and soul (ḥifẓ al-nafs wa al-'irḍ). This study confirms that chemical castration punishment cannot be used as a substantial and comprehensive solution to the problem of sexual crime, because it does not touch the structural or cultural roots of the problem.